2017
DOI: 10.1111/spc3.12364
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup conflict and barriers to common ground: A self‐affirmation perspective

Abstract: Psychological barriers to conflict resolution stem, in part, from defensive responses to feelings of self-threat. Self-affirmation theory proposes that affirmations of global self-worth-often achieved by writing or reflecting on core values-can broaden individuals' perspectives and potentially reduce biases in their intergroup judgments. In this paper, we review the extant literature on the use of self-affirmation to potentially reduce intergroup biases in order to shed light on the role of self-threat in perp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 70 publications
0
30
0
Order By: Relevance
“…Over the years, a significant body of literature has developed on psychological barriers to conflict resolution (Ross and Ward ; Kelman ; Bruneau and Saxe ; Bar‐Tal ; Bachar and Weiner ; Halperin ; Sherman, Brookfield, and Ortosky ). Intergroup conflict is a multidimensional phenomenon with a variety of causes, including historical grievances, unequal distribution of power and other resources, competing visions for the future, and incompatible ideologies (Bar‐Tal ; Klar and Branscombe ).…”
Section: Psychological Barriers and Intergroup Conflictmentioning
confidence: 99%
See 4 more Smart Citations
“…Over the years, a significant body of literature has developed on psychological barriers to conflict resolution (Ross and Ward ; Kelman ; Bruneau and Saxe ; Bar‐Tal ; Bachar and Weiner ; Halperin ; Sherman, Brookfield, and Ortosky ). Intergroup conflict is a multidimensional phenomenon with a variety of causes, including historical grievances, unequal distribution of power and other resources, competing visions for the future, and incompatible ideologies (Bar‐Tal ; Klar and Branscombe ).…”
Section: Psychological Barriers and Intergroup Conflictmentioning
confidence: 99%
“…To further organize our list of twenty‐six unique barriers, we created a typology based on research that distinguishes between the cognitive, affective, and motivated reasoning determinants of attitudes and beliefs (Kahneman and Tversky ; Halperin ; Sherman, Brookfield, and Ortosky ). Consistent with these proposed distinctions, our review of the literature on psychological barriers found that some scholars (e.g., Kahneman and Tversky ; Ross and Ward ) focused on “cognitive barriers,” while a second group (e.g., Halperin ; Halperin ) focused exclusively on emotion‐related barriers to conflict resolution, and a third group (e.g., Sherman et al ; Binning et al ; Sherman, Brookfield, and Ortosky ) emphasized the role that self‐enhancement might play in the creation of attitudes that promote positive self (or group) image at the cost of fueling intergroup conflict. Accordingly, we classified each of our twenty‐six unique barriers based on whether scholars had most strongly associated it with underlying psychological processes that were cognitive, affective, and/or motivated in nature.…”
Section: Types Of Psychological Barriers: Cognitive Affective and Mmentioning
confidence: 99%
See 3 more Smart Citations